Negative Polarity in ‮khl‬‎ Constructions in Qumran Hebrew - Miller, Cynthia L. (Dead Sea discoveries, 2020)
The Hebrew quantifier ‮כל‬‎ is used both as a universal quantifier (equivalent to English all) and as a distributive quantifier (equivalent to English each, every). In Qumran Hebrew, as in Biblical Hebrew, the quantifier ‮כל‬‎ occurs in four syntactic constructions depending upon the type of noun phrase that follows it in order to indicate nuances of individuation and specificity in addition to universal and distributive quantification. In contexts in which these constructions occur within the scope of negation, the quantifier assumes negative polarity (none, nothing, any in English). In this article, we identify the syntactic contexts and constructions in which negative polarity is licensed and we describe and analyze the constructions of ‮כל‬‎ with negative polarity. We also compare the negative polarity licensing exhibited in Qumran Hebrew with Biblical Hebrew and demonstrate that some of the features of negative polarity in Qumran Hebrew differ from those in Biblical Hebrew.